2012
DOI: 10.1111/j.1538-7836.2012.04808.x
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS‐13 activity and autoantibodies classes and subclasses as prognostic predictors in acquired thrombotic thrombocytopenic purpura

Abstract: ADAMTS-13 activity and autoantibodies classes and subclasses as prognostic predictors in acquired thrombotic thrombocytopenic purpura. J Thromb Haemost 2012; 10: 1556-65.Summary. Background: Thrombotic thrombocytopenic purpura (TTP) is a rare life-threatening disease. Of surviving patients, 45% develops an exacerbation or a late recurrence. Severe ADAMTS-13 deficiency, both during the acute episode and remission, is a well-established predictor of recurrence. The predictive value of anti-ADAMTS-13 antibodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 54 publications
(99 reference statements)
4
53
0
Order By: Relevance
“…Measurement of ADAMTS13 levels is helpful in the diagnosis. An ADAMTS13 level of no less than 5%, the absence of ADAMTS inhibitors, and expression of ADAMTS gene mutations will help confirm the diagnosis (48).…”
Section: Adamts In the Pathogenesis Of Obstetrics And Gynecology Disementioning
confidence: 99%
“…Measurement of ADAMTS13 levels is helpful in the diagnosis. An ADAMTS13 level of no less than 5%, the absence of ADAMTS inhibitors, and expression of ADAMTS gene mutations will help confirm the diagnosis (48).…”
Section: Adamts In the Pathogenesis Of Obstetrics And Gynecology Disementioning
confidence: 99%
“…15 A number of studies have shown that anti-ADAMTS13 antibodies detected in the plasma of TTP patients are composed of subclasses IgG1 and IgG4. 8,10,16,17 Isotype switching from IgM to IgG is a characteristic feature of the humoral immune response, which depends on help from CD41 T cells. 10,16 Anti-ADAMTS13 antibodies have undergone affinity maturation through somatic hypermutation in germinal centers.…”
Section: Introductionmentioning
confidence: 99%
“…1 A severe deficiency of the plasma enzyme ADAMTS13 (a disintegrin-like and metalloprotease with thrombospondin type-1 repeats), due to genetic mutations (congenital) 2 or anti-ADAMTS13 autoantibodies (acquired), 3,4 is the main mechanism in the pathogenesis of TTP. Autoantibodies against ADAMTS13 are predominantly of the IgG class, [5][6][7] particularly subclasses IgG4 and IgG1, [8][9][10] but autoantibodies belonging to classes IgM and IgA have also been described. 5,[9][10][11] Elevated levels of soluble circulating autoantibody-antigen immune complexes are the hallmark of many autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies against ADAMTS13 are predominantly of the IgG class, [5][6][7] particularly subclasses IgG4 and IgG1, [8][9][10] but autoantibodies belonging to classes IgM and IgA have also been described. 5,[9][10][11] Elevated levels of soluble circulating autoantibody-antigen immune complexes are the hallmark of many autoimmune diseases. [12][13][14] Deposition of circulating immune complexes in tissues, mainly in capillary beds, promoting inflammation and tissue damage, is the most relevant pathological mechanism underlying immune complex-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%